The effectiveness of group guidance services in improving social interaction among eighth grade students at budi agung Junior High School, Medan: An experimental study - Amalia, Sinta; Rusman, Abdul Aziz (Universitas Islam Negeri Raden Intan Lampung, 2025)
Social interaction plays a crucial role in student development, influencing communication skills, cooperation, and adaptability in the school environment. However, some students still struggle to interact with their peers, which can impact their social and academic development. One strategy to enhance students’ social interaction is group guidance services, which provide structured communication and group support. This study aims to analyze the effectiveness of group guidance services in improving the social interactions of eighth-grade students at Budi Agung Junior High School, Medan. This study employs a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The sample consists of 20 students divided into an experimental and a control group. The results indicate a significant improvement in the social interactions of the experimental group, with the average score increasing from 56.80 to 70.30, whereas the control group increased from 58.90 to 63.50. These findings demonstrate that group guidance services effectively enhance students’ social interactions. Therefore, their implementation is recommended in educational settings with more diverse approaches.